Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1161/atvbaha.109.198994
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis by Implantation of a Capillary Structure Constituted of Human Adipose Tissue Microvascular Endothelial Cells

Abstract: Objective-We previously reported a novel technology for the engineering of a capillary network using an optical lithographic technique. To apply this technology to the therapy of ischemic diseases, we tested human omental microvascular endothelial cells (HOMECs) as an autologous cell source and decellularized human amniotic membranes (DC-AMs) as a pathogen-free and low immunogenic transplantation scaffold. Methods and Results-Human umbilical vein endothelial cells were aligned on a patterned glass substrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…In this technique, a micro-scaled surface patterning technique with biofunctional materials and transfer cell printing technique were applied. We also confirmed that the engineered capillary-like structures were able to function as capillary vessels after implantation into experimental animals [16] . We concluded that this approach of applying a combination of bio-patterning and transfer cell printing techniques has big potential for engineering not only capillary vessels, but also various types of tissue components.…”
Section: Introductionsupporting
confidence: 75%
“…In this technique, a micro-scaled surface patterning technique with biofunctional materials and transfer cell printing technique were applied. We also confirmed that the engineered capillary-like structures were able to function as capillary vessels after implantation into experimental animals [16] . We concluded that this approach of applying a combination of bio-patterning and transfer cell printing techniques has big potential for engineering not only capillary vessels, but also various types of tissue components.…”
Section: Introductionsupporting
confidence: 75%
“…42 Furthermore, Resch et al 43 demonstrated that the stroma of the transplanted AM can integrate into the host corneal tissue. Recently, the AM was also used as a scaffold for the engineering of the capillary structure by printing technology, 44 suggesting that the AM, which is primary avascular tissue, could also be vascularized. All these promising findings illustrate the behavior of AM scaffolds in vivo and thereby set the promising background for the potential use of our highly differentiated tissue constructs in reconstructive urology.…”
Section: Fig 4 the Distribution Of Urothelial Differentiation-relatmentioning
confidence: 99%
“…10 Currently, an important tissue engineering strategy for the vascular and cardiac regeneration may be cell sheet technology, using either a temperature-responsive polymer or magnetic cell arrangement methods. 8,11,12 Clearly, the tissue printing method demonstrated herein by Yoshida et al 6 is an additional strategy for tissue engineering. For future clinical application, there may be several issues to be further studied.…”
Section: See Accompanying Article On Page 1300mentioning
confidence: 94%
“…In fact, direct implantation of adiposederived regenerative cells has been shown to stimulate angiogenesis and to mobilize endothelial progenitor cells in the setting of tissue ischemia. 5 In this issue of Arteriosclerosis, Thrombosis, and Vascular Biology, Yoshida et al 6 report that implantation of human omentum adipose tissue-derived microvascular endothelial cells (HOMECs) augmented angiogenesis in a mouse model of hindlimb ischemia. Moreover, a unique and new aspect of their research is that they used an engineered endothelial capillary network based on optical lithographic printing technique.…”
Section: See Accompanying Article On Page 1300mentioning
confidence: 99%
See 1 more Smart Citation